Educational Aspirations under Early Marriage:A Study of Yadav Female Adolescents - Dahal, Ram Chandra (GS WOW: Wisdom of Worthy Research Journal, 2025)
In South Asia, particularly among socially excluded groups, early marriage remains a major barrier to girls’ education. In Nepal, despite legal protections and development programs, adolescent girls from marginalized caste and ethnic communities—especially the Yadav population in Siraha District—continue to experience early marriage that disrupts schooling. This cross-sectional study examines the educational aspirations of Yadav girls aged 10–19, comparing married and unmarried students. Data were collected through structured questionnaires from a random sample of 300 participants and analyzed using descriptive statistics and mean-score comparisons. Findings show that 85 percent of respondents highly value education and aspire to complete secondary or higher levels. However, married girls reported heavier domestic responsibilities, irregular attendance, and reduced emotional, household, and financial support from spouses and in-laws compared with unmarried peers (p < 0.05). Poverty, family neglect, and social pressure to marry emerged as key constraints. The study highlights the tension between educational aspirations and early marriage, emphasizing the need for community-based strategies to delay.